Megymenum tuberculatum, a new species of Megymenini from Java and a review of distribution of M. brevicorne (Hemiptera: Heteroptera: Dinidoridae) - Hemala, Vladimír; Kocorek, Anna; Lis, Jerzy A. (Zootaxa, 2020)
Megymenum tuberculatum Hemala & Kocorek, sp. nov. (Hemiptera: Heteroptera: Dinidoridae: Megymeninae: Megymenini) from Java (Indonesia) is described, illustrated and compared with M. brevicorne (Fabricius, 1787). Although the description is based on only one female specimen, the differences in the morphology of head, pronotum, and spermatheca are significant. In addition, M. brevicorne is briefly redescribed and its distribution and biology reviewed along with its first record from Nepal.